Effects of lubricant on evaporation and boiling processes of R1234ze(E): A molecular dynamics study. (5th July 2021) - Cai, Shouyin; Wu, Chuang; Li, Xiaoxiao; Li, Qibin
Highlights: Boiling process of refrigerant/lubricant mixture is investigated from microscopic. The heat transfer capacity of mixture system is evaluated by thermal resistance. Temperature jump and thermal resistance length increase with lubricant increasing. An oil film formed on Cu surface weakens the heat transfer capacity at interface. Abstract: Lubricant plays an important role in thermodynamic systems to lubricate the sliding surfaces. However, the mixing of working fluid and lubricant will significantly affect the heat transfer capacity of the system. Therefore, molecular dynamics simulations are employed to investigate the effects of lubricant PEC4 on the evaporation and boiling processes of R1234ze(E) in this paper. The results indicate that the evaporation and boiling process of R1234ze(E) is suppressed by the addition of PEC4 molecules. Additionally, PEC4 molecules will gradually replace R1234ze(E) molecules to absorb on Cu surface with the increase of PEC4 mass fraction. Then, an oil film will be formed on Cu surface and weaken the heat transfer capacity at the fluid–solid interface. The thermal resistance length is employed to evaluate the heat transfer capacity of the system. The result shows that the increase of the mass fraction of PEC4 will lead to an increase of temperature jump and thermal resistance length, which weakens the heat transfer capacity. Moreover, the strong attractive interactions between PEC4 and Cu substrate will lead to the formation of oil film on the Cu surface during the evaporation and boiling processes, which will result in heat transfer deterioration.